Gellius the satirist : Roman cultural authority in Attic nights - Keulen, Wytse Hette. (Mnemosyne, Supplements, 2009)
This monograph presents an original portrait of the second-century miscellanist Aulus Gellius, based on a detailed reading of Attic Nights against its contemporary background. Highlighting Gellius' use of humour and irony in his portrayals of controversial celebrities such as Favorinus and Herodes Atticus, the book provides a necessary corrective to interpretations of Gellius as an uncritical philhellene or an apolitical bookworm. Distinguishing Gellius' various literary personae (the youthful sectator, the independent researcher, the mature writer and adviser), the book uncovers the many-layered sophistication of Gellius' self-presentation. Noting previously unrecognised allusions to literary works and contemporary events, it offers a fresh perspective on Gellius as a satirical writer, whose Roman cultural programme reflects the ambiguities and complexities of Antonine intellectual life.